Prevention of tumors in treating fibrocystic breast diseases using Vitex agnus-castus-based herbal remedy - N. A. Omarbayeva; D. R. Kaidarova; D. Kh. Omarov; A. Askandirova; Kh. Keskin; A. Zh. Abdrakhmanova; S. A. Yessenkulova; T. G. Goncharova; A. K. Jakipbayeva (Опухоли женской репродуктивной системы, 2025)
Background. Oncologists notice an increasing prevalence of female reproductive system pathological conditions that lead to benign and malignant diseases of mammary glands. Fibrocystic breast diseases (FBD) occur in approximately 80 % of women of reproductive age worldwide. Currently, there is no single widely accepted treatment for FBD. The therapy mainly includes surgery and hormonal treatment. A few herbal medicines effective against FBD include Vitex agnus-castus (VAC) medications. According to many studies, the absence of timely targeted preventive therapy puts patients with FBD at risk of developing malignant tumors. FBD is a risk factor for cancer development and turns into cancer in 3–6 % of patients.Aim. To assess the effectiveness of VAC against FBD.Materials and methods. In this study, 150 women aged 40+ with FBD were randomly assigned to the treatment group (n = 78) or the controls (n = 72). The groups were similar in demographic characteristics, including age, parity, menopause, history of abortions, family history of breast cancer, and alcohol and tobacco consumption. The treatment group received two tablets of VAC extract (each containing 162 mg) daily for six months. At baseline, weeks 12 and 24, all participants were evaluated using a visual analog scale and ultrasound examination.Results. Breast pain decreased significantly in the treatment group, and the median visual analog scale scores at weeks 12 and 24 decreased significantly compared to baseline in the treatment group (89.7 % at baseline, 76.9 % at week 12, and 42.3 % at week 24) compared to the controls (66.3 % at baseline, 63.9 % at week 12 and 61.1 % at week 24). Furthermore, the breast ultrasound findings at weeks 12 and 24 revealed that regression rates in the treatment group were significantly higher than in the control arm (46.2 % vs. 6.9 % at week 12; 55.1 % vs. 8.3 % at week 24).Conclusion. VAC is effective in managing patients with FBD. VAC treatment efficacy can be evaluated using a visual analog scale and ultrasound examination. The herbal remedy VAC extract used in this treatment for patients with FBD has proven effective in preventing breast cancer.